The coconut tree has more to offer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Promoting Multi-purpose Uses and Competitiveness of the Coconut. PA Batugal, VR Rao, and C Bong. 1998. 190 pp. ISBN 92 9043 382 5